Preference of Suture Specifications in a Selected Periodontal and Implant Surgeries in Turkey - Koyuncuoglu, Cenker Zeki; Yaman, Duygu; Kasnak, Gokhan; Demirel, Korkud (European Journal of Dentistry, 2019)
Objective Various suture materials and needles are now available for use in the dental surgery. The aim of this study was to determine the preference of suture materials among Turkish dentists by a dental survey.Materials and Methods The survey was prepared and sent electronically to Turkish dentists through e-mail and/or Facebook. Dentists were asked to report their graduation year from dental school and their specialty if they have one. In addition, the type periodontal/implant operations and the frequency of those operations applied by them were questioned. The participants were to indicate their suture preferences for these procedures in a multiple-choice questionnaire.Results Fifty-seven regular dentists, 49 periodontists, 22 oral surgeons, and 8 other specialists completed a self-administered survey. The majority of clinicians worked in private practice (77.9%). Nonabsorbable sutures were the most preferred for all procedures except periodontal plastic surgery. In regenerative surgeries, monofilament, 5–0 diameter suture material on a reverse cutting, 3/8 circle needle was preferred. In addition, for mucogingival surgery, 5–0 diameter suture material on a reverse cutting and 3/8 circle needle was favored. For dental implants, 4–0 diameter suture material on a reverse cutting and 3/8 circle needle was preferred. Monofilament and braided sutures were selected almost equally for implant operations.Conclusions In periodontal and implant surgeries, dentists highly preferred the use of nonabsorbable sutures. In addition, the shape and diameter of needle had an important role in the selection of suture material. The present study's results may serve as a guide for the future studies.
Keywords: implant surgeries; periodontal operations; suture types